The measurement of photoneutron dose around an 18 MV Varian linear accelerator by TLD600 and TLD700 dosimeters inside the polyethylene sphere of neutron probe LB 6411 - F, Samiei; A, Nedaie H; H, Darestani; N, Banaee; N, Shagholi; K, Mohammadi; A, Shahvar (JOURNAL OF ADVANCES IN PHYSICS, 2014)
Bremsstrahlung X-rays from high-energy linear accelerators (Linacs) produce neutrons as a result ofphotonuclear reactions mainly with the different materials constituting the accelerator head. The neutronsproduced during high energy radiotherapy should be considered in terms of protection and ose escalation. Due to the very intense photon component in the Linac field causing pulse pile-up and dead-time effects indetectors, measurement of the corresponding neutron dose by active dosimeters is extremely troublesome. In this study, the neutron probe LB 6411, which active detector of 3He proportional counter tube was replaced withthe passive detectors of TLD600 and TLD700, has been used to perform neutron measurements at four pointsaround the 18 MV Varian 2100C Linac facility. The neutron dose equivalent at the distance of 1 and 2 m fromthe isocentre on the patient couch was obtained 2.2 and 0.75 mSv.Gy-1respectively. According to the results,the dose equivalent from emitted photoneutrons is not negligible and therefore treatment conditions should beoptimized. The results of this study emphasized that TLD600 and TLD700 dosimeters inside the polyethylenesphere of neutron probe LB 6411 is an appropriate choice for studying photoneutron production in the vicinity ofthe accelerator